Off-label drug prescriptions in French general practice: a cross-sectional study. Issue 4 (9th April 2019) - Drogou, François; Netboute, Allison; Giai, Joris; Dode, Xavier; Darmon, David; Kassai, Behrouz; Letrilliart, Laurent
Abstract : Objectives: Off-label drug prescribing is a public health and economic issue. The aim of this study was to describe off-label prescription in general practice in France, in terms of frequency and nature, and to identify its main determining factors. Design: Multicentre cross-sectional study Setting: Twenty-three training general practice offices Participants: All the voluntary patients coming for a medical consultation or visited at home over a cumulative period of 5 days per office between November 2015 and January 2016. Methods: Eleven interns, acting as observers, collected data. Two reviewers analysed the drugs prescribed by the trainers, in order to identify those prescribed off-label in terms of their indication or the age of the patient. We used a univariate, then a multivariate model, based on hierarchical mixed-effects logistic regression. Results: Among the 4932 drug prescriptions registered, 911 (18.5%[95% CI17.4% to 19.6%]) were off-label, of which 865 (17.6%) due to the indication of the drug and 58 (1.2%) due to the age of the patient. The prescription never mentioned the off-label use, neither was the patient informed of it, as required by the French law. With the multivariate analysis, variables contributing to off-label prescription were the number of drugs (OR=1.05 for each additional drug), the initiation of new drug therapy (OR=1.26) and the non-specific goal of the prescription (OR=1.43); the age of the patient ≤14 years (OR=1.42); the rural location of the physician's practice (OR=1.38) and the low frequency of the visits of national health insurance representatives (OR=0.93). Conclusion: Almost one out of five drugs prescribed in French general practice was off-label. It seems necessary to better train physicians in clinical pharmacology, to provide them with more effective drug prescription software, to reinforce postmarketing surveillance and to clearly define off-label use by consensus.